Home Assistant With IoT Smart Solution For Smart Home - Sukma Rizki; Muhammad Fikry; M Ishlah Buana Angkasa; Fajar Rivaldi Chan (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The advent of Internet of Things (IoT) technology has revolutionized various aspects of everyday life, particularly within the home environment. IoT-powered home assistants represent one of the primary implementations, offering intelligent automation and control solutions that enhance the modern home experience. This paper explores the implementation of IoT-based home assistants to improve convenience, security, and energy efficiency in smart homes. In addition, the challenges and future directions for the development of this technology are examined, with a focus on key areas such as device interoperability, data privacy and security, and user experience optimization. As demand for smart home solutions continues to rise, the integration of cloud computing, artificial intelligence (AI), and advanced communication protocols will further drive innovation in this field.